Bcl‐3 induced by IL‐22 via STAT3 activation acts as a potentiator of psoriasis‐related gene expression in epidermal keratinocytes. Issue 1 (20th November 2017) - Tohyama, Mikiko; Shirakata, Yuji; Hanakawa, Yasushi; Dai, Xiuju; Shiraishi, Ken; Murakami, Masamoto; Miyawaki, Saori; Mori, Hideki; Utsunomiya, Ryo; Masuda, Kana; Hashimoto, Koji; Sayama, Koji
Abstract: IL‐22 induces STAT3 phosphorylation and mediates psoriasis‐related gene expression. However, the signaling mechanism leading from pSTAT3 to the expression of these genes remains unclear. We focused on Bcl‐3, which is induced by STAT3 activation and mediates gene expression. In cultured human epidermal keratinocytes, IL‐22 increased Bcl‐3, which was translocated to the nucleus with p50 via STAT3 activation. The increases in CXCL8, S100As and human β‐defensin 2 mRNA expression caused by IL‐22 were abolished by siRNA against Bcl‐3. Although CCL20 expression was also augmented by IL‐22, the knockdown of Bcl‐3 increased its level. Moreover, the combination of IL‐22 and IL‐17A enhanced Bcl‐3 production, IL‐22‐induced gene expression, and the expression of other psoriasis‐related genes, including those encoding IL‐17C, IL‐19, and IL‐36γ. The expression of these genes (except for CCL20) was also suppressed by the knockdown of Bcl‐3. Bcl‐3 overexpression induced CXCL8 and HBD2 expression but not S100As expression. We also compared Bcl‐3 expression between psoriatic skin lesions and normal skin. Immunostaining revealed strong signals for Bcl‐3 and p50 in the nucleus of epidermal keratinocytes from psoriatic skin. The IL‐22‐STAT3‐Bcl‐3 pathway may be important in the pathogenesis of psoriasis. Abstract : IL‐22 mediates psoriasis‐related gene expression. Bcl‐3 is involved in the signaling mechanism leading from pSTAT3 to the expression of these genes. The IL‐22‐STAT3‐Bcl‐3 pathway may be important in the pathogenesis of psoriasis.